Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru di Sekolah SMA Swasta Kampus HKBP Nommensen Pematangsiantar: Penelitian - Septianus Simarmata; Jatenra Hutahaean; Ririn Tampubolon; Theresia Sigiro; Ruth Angelina Pardede; Kamucia Marbun; Septinar Silalahi; Susy Alestriani Sibagariang (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the effect of principal leadership on teacher performance in the implementation of the Field Experience Program (PPL) at SMA Swasta Kampus Nommensen, Pematangsiantar City. The research employed a quantitative approach using a descriptive associative method. The population of this study consisted of all teachers at SMA Swasta Kampus Nommensen, totaling 32 teachers, and all members of the population were included as research samples using a total sampling technique. Data were collected through a five-point Likert-scale questionnaire developed based on indicators of principal leadership and teacher performance. Principal leadership was measured through indicators including directing ability, communication skills, decisiveness in decision-making, role modeling, and professional development of teachers. Meanwhile, teacher performance was assessed based on indicators such as discipline, responsibility, teaching competence, collaboration, and instructional innovation. Data analysis involved instrument validity and reliability tests, prerequisite assumption tests, and simple linear regression analysis using SPSS version 27. The results revealed that the data were normally distributed and the regression model was considered feasible. Teachers’ responses to the PPL questionnaire were predominantly in the Agree and Strongly Agree categories, with positive responses reaching 50.1%, indicating that principal leadership and teacher performance were at a fairly good level. Hypothesis testing demonstrated that principal leadership had a significant effect on teacher performance. These findings suggest that effective principal leadership contributes to improved teacher performance in the implementation of the Field Experience Program. However, further improvement is still required, particularly